2016
DOI: 10.1007/jhep06(2016)097
|View full text |Cite
|
Sign up to set email alerts
|

Chern-Simons actions and their gaugings in 4D, N =1 superspace

Abstract: Abstract:We gauge the abelian hierarchy of tensor fields in 4D by a Lie algebra g. The resulting non-abelian tensor hierarchy can be interpreted via a g-equivariant chain complex. We lift this structure to N = 1 superspace by constructing superfield analogs for the tensor fields, along with covariant superfield strengths. Next we construct Chern-Simons actions, for both the bosonic and N = 1 cases, and note that the condition of gauge invariance can be presented cohomologically. Finally, we provide an explicit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(52 citation statements)
references
References 31 publications
(58 reference statements)
5
47
0
Order By: Relevance
“…1 They also showed CS actions in the case of non-Abelian tensor hierarchy [17]. 2 In this paper, we use the term "prepotentials" to refer to superfields which consist of the bosonic gauge fields and field strengths as well as their superpartners.…”
Section: Review Of the Covariant Approachmentioning
confidence: 99%
“…1 They also showed CS actions in the case of non-Abelian tensor hierarchy [17]. 2 In this paper, we use the term "prepotentials" to refer to superfields which consist of the bosonic gauge fields and field strengths as well as their superpartners.…”
Section: Review Of the Covariant Approachmentioning
confidence: 99%
“…At this point the non-abelian tensor hierarchy is a g-equivariant super-de Rham complex of forms on X × Y . Its Chern-Simons-like invariant was studied in some detail and generality in [7]. We review the gauge transformations, g-covariant superfield strengths, Bianchi identities, and Chern-Simons action in section 3.1.…”
Section: Jhep12(2016)085mentioning
confidence: 99%
“…The first is the superspace Chern-Simons invariant (3.5) of the gauged tensor hierarchy of the eleven-dimensional 3-form. This tensor hierarchy is a g-equivariant superspace chain complex with g the algebra of diffeomorphisms on Y [6,7]. The second is a superspace version of the Hitchin functional for G 2 -structure manifolds (3.8).…”
Section: Jhep12(2016)085mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it was explicitly shown that it does work for 10D super-Yang-Mills in [24]. More recently, the approach was extended to the far more subtle case of elevendimensional supergravity in [25][26][27][28][29][30].…”
mentioning
confidence: 99%